Assessment of the Distribution of Rectal Carriage of Virulence and Carbapenemases Genes in Patients Enrolled for Planned Hospitalization - I. V. Lazareva; P. S. Starkova; V. A. Ageevets; M. O. Volkova; M. S. Lebedeva; A. S. Navatskaya; E. B. Myasnikova; G. V. Mitroshina; S. V. Sidorenko (Антибиотики и Химиотерапия)
Klebsiella pneumoniae is the most common cause of nosocomial infections. There are two main types of K.pneumoniae (Kp) - classical K.pneumoniae (cKp) and hypervirulent K.pneumoniae (hvKp). In 2015, an outbreak of nosocomial infections caused by Kp was recorded in China for the first time, showing signs of hypervirulence and multidrug resistance (production of blaKPC-2). The purpose of this work is to assess the frequency of rectal colonization of patients admitted to a planned treatment in a cancer hospital with virulent and multidrug resistant strains of Kp and Pseudomonas aeruginosa. The study included 168 patients, 156 isolates of gram-negative bacteria were isolated from their rectal samples. Only one P.aeruginosa isolate turned out to be a blaVIMproducer. 30 isolates of Klebsiella spp.: Kp n=25; K.oxytoca n=3; K.planticola n=1; K.variicola n=1. Producers of carbapenemases have not been identified among them. Hypervirulence markers were detected in two of the three K.oxytoca isolates: in one (string-test «-») - all 5 genes (iucA,prmpA,prmpA2, iroB,peg-344), as well as two additional virulence genes, terB and irp2; in the second (string-test «+») - rmpA and irp2. A hypermucoid phenotype was observed in six Kp isolates and one K.oxytoca. Markers of hypervirulence, presumably with plasmid localization, were found in the Kp isolates: iucA (aerobactin), n=3; prmpA (hypermucoid phenotype regulator), n=3; iroB (salmohelin), n=2; and also, peg-344 (inner membrane conveyor), n=4; virulence determinants of presumably chromosomal localization: terB, n=1 and irp2, n=8. TerB and irp2 were also found in the K.variicola isolate. It is obvious that rectal carriage of bacteria is a real problem as it may be a constant reservoir and source of virulence genes, along with resistance genes.